Political, economic and social introduction of Suriname - Pigot, C. A. F. (2009)
Briefly describes the political, economic and social situation in Suriname. Looks at the stages in the development planning of Suriname. Presents some thoughts about the world's development paradigm and Suriname in the 21st century.